2009
DOI: 10.1371/journal.pbio.1000023
|View full text |Cite
|
Sign up to set email alerts
|

Input Subsidies to Improve Smallholder Maize Productivity in Malawi: Toward an African Green Revolution

Abstract: Recent hikes in food prices have created economic and social turmoil in many African countries. But in Malawi, fertilizer and seed subsidies have enabled small-scale farmers to improve maize productivity and achieve food security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
270
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(287 citation statements)
references
References 14 publications
3
270
0
1
Order By: Relevance
“…The Malawi government is exploring adding legume seed to the portfolio of subsidized inputs (8). There are, however, challenges to this strategy, as shown by our experimentation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The Malawi government is exploring adding legume seed to the portfolio of subsidized inputs (8). There are, however, challenges to this strategy, as shown by our experimentation.…”
Section: Discussionmentioning
confidence: 96%
“…Africa faces declining agricultural capacity just as anthropogenic-driven reductions in rainfall are enhancing risk (7). A hopeful exception is underway in Malawi where the first African green revolution has been hailed (8). To address chronic food insecurity in this impoverished population of 13 million, the government has subsidized N-fertilizer and improved maize seed (90% of cost), and enhanced access by over a million farmers annually since 2006.…”
mentioning
confidence: 99%
“…This resulted in a doubling of cereal yields in developing countries between 1960 and 1990 [6]. Fifty years on, and the benefits of this revolution appear to have peaked: the global population since the 1960s has more than doubled, fresh water shortages hinder large-scale irrigation, and further fertilizer application would be damaging in both crop yield and environmental terms (as well as being economically unfeasible in many third-world countries without considerable subsidies) [7]. The demand for biofuels (in such circumstances where the production of such fuels directly competes with arable land) can also reduce the area of arable land that can be dedicated to food production [8].…”
Section: Why Bother?mentioning
confidence: 99%
“…The country of Malawi introduced a national subsidy program in 2005, providing vouchers for one bag of urea and one bag of diammonium phosphate fertilizers-for one acre of land. Within a few years, there was dramatic increase in food production, primarily maize (Denning et al 2009). Although there is not yet conclusive evidence that this has led to decreased undernutrition in Malawi, a study of several sites in Africa showed increased food security and diet diversity three years after a fertilizer subsidy program was introduced (Remans et al 2011).…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%